DESAIN PRODUK, HARGA DAN GAYA HIDUP HALAL TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA SEPEDA LISTRIK - Sidanti, Heny; Sulistiyowati, Liliek Nur; Astutik, Ristania Febriola (IAIN Ambon, 2024)
This study aims to determine the effect of product design, price and lifestyle on purchasing decisions for electric bicycle users in Madiun City. The research method used is quantitative research. The research location or data collection was carried out on users of electric bicycle products in Madiun City through online media by distributing questionnaires using google form with a sample of 384 respondents. Data was collected through a questionnaire based on a Likert scale of 1-5. The data was analyzed using multiple linear regression analysis with the help of the SPSS version 27.0 application. The results of this study prove that product design has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, lifestyle has a positive and significant effect on purchasing decisions.